L’adultère à l’ère numérique : Une discussion sur la non/monogamie et le développement des technologies numériques à partir du cas Ashley Madison - Nathan Rambukkana; Maude Gauthier (Genre, Sexualité et Société)
This interview with Nathan Rambukkana uses the case of the ‘cheating website’ Ashley Madison to address the broader topic of digital intimacies. It references concepts, critical approaches and analyses that he develops in his book Fraught Intimacies, which explores the mediation of non-monogamies (how they are represented and discussed in the public sphere). The interview also mobilizes his current work on digital intimacies, including an interest for avatar infidelity. Infidelity, heteronormativity and non/monogamy are at the heart of this article, as well as the transformations brought by the digital. The interview addresses these transformations in relation to the adultery industry and interrogates practices of surveillance, hacking and privacy in the digital context. It also addresses the effects of these developments on human lives.